Consumer Protection in Cyberspace - Oscar H. Gandy, Jr. (tripleC: Communication, Capitalism & Critique, 2011)
This critical essay introduces the problem of discrimination enabled through the use of transaction-generated-information derived from the analysis of user behaviors within the network environment. The essay begins by describing how segments of the population that are already vulnerable become further victimized through the strategic use of discriminatory algorithms in support of identification, classification, segmentation, and targeting. In response, it evaluates a set of policy options that might be used to limit the harm and compensate the victims of these inherently dangerous technologies. Traditional approaches that stress the protection of privacy through restrictions on the collection and use of personal information are compared with alternatives based on individual and class actions under tort law, as well as more traditional regulatory approaches developed in the area of consumer products safety and environmental regulation.